2020
DOI: 10.1177/1098612x20969485
|View full text |Cite
|
Sign up to set email alerts
|

Biological variation of total thyroxine (T4), free T4 and thyroid-stimulating hormone in 11 clinically healthy cats

Abstract: Objectives The aim of this study was to investigate the biological variation of total thyroxine (T4), free T4 (fT4) and thyroid-stimulating hormone (TSH) in 11 clinically healthy cats aged between 3 and 15 years old, in Sydney, Australia. Methods Blood was collected weekly for up to 6 weeks and serum T4, fT4 and TSH concentrations were analysed using canine-specific reagents. Restricted maximum likelihood was used to estimate within-subject, between-subject and analytical variance components, which were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 37 publications
(60 reference statements)
4
14
6
Order By: Relevance
“…The CV G for free T 4 varies substantially between studies and was less in the current year-long study (7.1%) compared to the previous 6-week-long studies by us using the same methodology (13.4%) 10 and others using a different methodology (31.8%). 11 CV G for total T 3 was less than our previous short-term study. 10 Potential explanations in differences in CV G between studies include differences in biological variability with sampling interval and overall duration of the study, differences in homogeneity between study populations of cats, trends towards development of subclinical thyroid disease or disease affecting thyroid hormones, different assay methodologies used for total and free T 4 , and sampling at different geographical locations during different seasons.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…The CV G for free T 4 varies substantially between studies and was less in the current year-long study (7.1%) compared to the previous 6-week-long studies by us using the same methodology (13.4%) 10 and others using a different methodology (31.8%). 11 CV G for total T 3 was less than our previous short-term study. 10 Potential explanations in differences in CV G between studies include differences in biological variability with sampling interval and overall duration of the study, differences in homogeneity between study populations of cats, trends towards development of subclinical thyroid disease or disease affecting thyroid hormones, different assay methodologies used for total and free T 4 , and sampling at different geographical locations during different seasons.…”
Section: Discussioncontrasting
confidence: 76%
“…These studies observed greater interindividual variation relative to intraindividual variation with intermediate to high IoIs. [9][10][11] Collectively, these shortterm studies of biological variation suggested that it is important for clinicians to consider using RCVs to appreciate important biological changes in serial measurement of TSH and thyroid hormones, especially in cats with clinical concern for emerging thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerable data exist describing biological variation of biochemical analytes has been extensively described in people, 2,26,27 but less so in veterinary species, including cats. [7][8][9][10]16,28 This study builds upon previous work that evaluated biological variation weekly or with variable frequency over 42-100 days 7-10 by determining the biological variation of 19 biochemical analytes in clinically healthy cats sampled every 8 weeks over 1 year.…”
Section: Discussionmentioning
confidence: 99%